Comparison of speed and power of soccer players before the preparation period and during the soccer season - Mariusz Miłek; Radosław Perkowski (Kazimierz Wielki University, 2024)
Introduction. The article discusses the importance of speed and power in football and the need for appropriate training and load monitoring to minimise risk of injury. A comparative analysis of the players' speed and power indicators before and during the season was presented, suggesting the importance of dynamic physical adaptations in the face of the demands of the competition. Aim. The aim of the study was to investigate whether soccer players could improve their speed and strength through soccer training in a relatively short preparation period. Material and methods. The study involved 41 adult male footballers from the IV and III leagues, aged between 18 and 34, undergoing speed and power assessments. Speed was measured over a distance of 20 metres with additional measurements at 5 and 10 metres, while power was assessed by a long jump from a standing position, taking into account the stability of the landing. Results. Statistical analysis showed no significant differences in speed at 5 and 10 metres between terms I and II, but significant differences were observed in speed at 20 metres, where the average time decreased by 0.04 seconds. In contrast, the power test showed significant differences, increasing by 2.85 W in term II. There were no significant differences in speed and power relative to field position or correlation with age, although a weak positive correlation was observed between age and speed for 20 metres in term II and a weak negative correlation between age and the difference in the power test between terms. Conclusion. The analysis showed significant differences in power tests between terms, as well as differences in speed at 20 metres between defensive and offensive players. There were no significant correlations of age with test results, but a weak positive correlation was observed between age and speed at 20 metres in the 2nd term and a weak negative correlation between age and differences in the power test between terms.